Kodifiering av multietniskt ungdomsspråk - Helgason, Jon; Sköldberg, Emma (Nordiske Studier i Leksikografi, 2018)
This article covers some of the findings of a pilot study of what we per-ceive to be a tendency towards a codification of the contemporary urban vernacular in written Swedish. In Sweden, the urban vernacular has tradi-tionally been described as a youth language, and, as such, studied as a part of an (ephemeral) youth culture. However, both internationally and in Sweden there are claims to treat the urban vernacular as an urban dia-lect or ethnolect. This article contains a brief presentation of some the materials of this pilot study, as well as an account of three lexical items and how they are described in (mostly user-generated) lexicographical re-sources.